Visible learning technologies in literary-artistic education of high school students: impact on the reception and interpretation of the literary text - Paula Tamara CIOBICA (Acta et Commentationes, Sciences of Education, 2026)
Visible learning technologies represent an innovative pedagogical approach that supports active student engagement and enhances the interpretative process in literary education. This study examines the role of visual learning tools, such as concept maps, analytical worksheets and metacognitive journals, in improving the reception and interpretation of literary texts among high school students. The research combines theoretical analysis with case study observations conducted in literature classes. The results highlight increased motivation, improved critical thinking, and stronger metacognitive awareness in students.